O comportamento dos partidos na Câmara dos Deputados e no Senado Federal (1991-2007) - Geralda Luiza de Miranda (2008)
The thesis develops an empirically based explanation for the variation in the voting behavior of Brazilian parties in roll calls in the Câmara dos Deputados and in the Senado Federal. Assuming that party discipline is positively related to the amount of leeway in conducting legislative and voting processes granted the President and party bosses, the explanation explores the following propositions: 1) stimuli derived from the electoral arena influence the chain of delegation when it comes to actual voting; 2) such stimuli and others deriving from the party organization, in combination with the party directives in its dealings with the government, explain some of the variation in party discipline in each legislative house; 3) taking each legislative house as the unity of research, the variation is positively related to differences in the level of autonomy granted the party leaders. The explanation thus focuses on the institutions both from their internal and external dynamics. Chapter 2 shows how formal regulation of the principle of representation providesstimuli to delegating power to party leaders in the Câmara dos Deputados and in the Senado Federal. Research findings indicate that procedural provisions aiming at facilitating collective action induce to wider extension of delegation in the lower house than it is the case in the Senado. Following these findings, chapter 3 compares the regimental prerogatives of party leaders in both houses. This analysis leads to theconclusion that members of the lower house must rely more on the support of party leaders in order to maximize their preferences when specific policies are voted and when vying for political offices than it is the case with senators. However, when tested, the hypothesis that parties display greater discipline in the Câmara than in the Senado was not proved. When comparing regimental prerogatives, one finds that some changes in prevailing rules enhance the power of the parties as such. We argue that such changes do not derive from practical imperatives of collective action. Chapter 4 focuses on the delegation to the executive branch of government, following a line of explanation developed by Shugart and Carey (1992), who assume that this prerogative is linkedto the delegation to parties. We detected rule alteration aiming at increasing the control over the power of delegation as established in 1988 or at minimizing its range. These alterations are seen as setting a new pattern of balance between the legislative and the executive branches of government. Taking this institutional framework as a background, an interpretation of the dynamics of presidential andcongressional elections is presented in chapter 5. Research findings at this level show that stimuli derived from coalitions and electoral outcomes, as well as from negotiations concerning voting in roll calls explain both constitutional and regimental changes and observed variation in party discipline in the lower and upper legislative houses.The research findings highlight three main features of the present-day Brazilian political system. First, the consolidation of parties, especially the ones competing in presidential elections. Given the political efficiency of this level of elections and their influence over congressional elections, the politicians who run more than once tend to favor centralization in their strategies to influence electoral and parliamentary arenas. From this analytical perspective, the conclusion that Brazilian political partiesare poorly institutionalized, mostly provincial in their performance, decentralized and feckless must be qualified. Second, a new pattern of balance between the legislative and the executive branches of government is under way. The procedures of the delegation to legislate are being altered due to influences stemming from the electoral arena and this process of change points to the strengthening of thelegislative branch of government in its dealings with the executive. Third, the research findings also show that party discipline and the growing importance of parties in the congressional dynamics are not independent from incentives connected to the electoral arena, that is, while the existing electoral laws enhance political parochialism, the actual dynamics of elections stimulates strategies of concerted action in the electoral and parliamentary arenas.